1982
DOI: 10.1111/1523-1747.ep12497912
|View full text |Cite
|
Sign up to set email alerts
|

Functional Evidence for Complement-activating Immune Complexes in the Skin of Patients with Bullous Pemphigoid

Abstract: Previous immunofluorescent studies showing deposits of immunoglobulin and complement at the cutaneous basement membrane zone have provided evidence supporting a role for immune complexes in the pathogenesis of bullous pemphigoid. In this study the functional activity of the deposits has been examined using leukocyte attachment, a method for detecting and quantitating the biological activity of complement-activating immune complexes in tissues. When peripheral blood leukocytes suspended in serum complement were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1984
1984
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…This resulted, in fact, in an increased in¯ux of neutrophils into the upper dermis of the graft, but not in subepidermal blisters. In contrast to acantholysis in pemphigus, blister formation in BP requires in¯ammatory cells and mediators in addition to autoantibodies [27,31,32]. One may speculate that SCID mice lack suf®cient numbers of in¯ammatory cells, necessary for BP blister formation.…”
Section: Discussionmentioning
confidence: 99%
“…This resulted, in fact, in an increased in¯ux of neutrophils into the upper dermis of the graft, but not in subepidermal blisters. In contrast to acantholysis in pemphigus, blister formation in BP requires in¯ammatory cells and mediators in addition to autoantibodies [27,31,32]. One may speculate that SCID mice lack suf®cient numbers of in¯ammatory cells, necessary for BP blister formation.…”
Section: Discussionmentioning
confidence: 99%
“…Manipulations that interfered with complement activation also resulted in a drastic reduction of neutrophil influx into the dermis of the animals (13), suggesting that neutrophils may play a key role in blister formation in the experimental BP/HG model. Previous findings reported by Gammon et al (14) using an in vitro model of BP led to the hypothesis that subepidermal blistering in BP is dependent upon antibody binding to an antigen of the DEJ, complement activation and an inflammatory infiltration of lesional skin. These investigators showed that, when cryosections of normal human skin were incubated in an organ culture system with a BP serum plus an exogenous source of complement and human peripheral blood leukocytes, the inflammatory cells migrated and attached to the DEJ in these sections.…”
Section: Introductionmentioning
confidence: 98%
“…The differential expression of intensity between IgG and C3 among the above disorders is not understood. [81][82][83] Multiple deposits at the BMZ. This pattern of deposition strongly favors EBA (Fig 4, A) and bullous SLE over the pemphigoid group of diseases.…”
mentioning
confidence: 99%